Students’ Perception Toward Self-Regulated Learning in Online Writing Class - Dewi M, Cantika Sari; Masitoh, Fitriatul; Afifi, Nur; Qamaria, Rezki Suci (Metathesis: Journal of English Language, Literature, and Teaching, 2023)
Self-regulated learning expresses students' efforts to systematically regulate metacognitive, motivational, and behavioural activities in learning. Self-regulated learning is considered an essential element in the success both in online learning and EFL learning especially learning writing. The purpose of this study is to find out how the level of students’ perception toward self-regulated learning in online writing class. This study was quantitative research and the design used was survey research. The questionnaire was used to collect the data in this study. The sample of this study was 100 students of English Education Department of IAIN Kediri class of 2020. The results showed that most students have the high level of perception toward self-regulated learning in online writing class. The high students’ perception indicated that students can be directed to be self-regulated in online writing class and can still develop their writing skill.